The circular RNA ciRS‐7 promotes APP and BACE1 degradation in an NF‐κB‐dependent manner. (13th March 2017) - Shi, Zhemin; Chen, Ting; Yao, Qingbin; Zheng, Lina; Zhang, Zhen; Wang, Jingzhao; Hu, Zhimei; Cui, Hongmei; Han, Yawei; Han, Xiaohui; Zhang, Kun; Hong, Wei
Abstract : The aberrant accumulation of β‐amyloid peptide (Aβ) in the brain is a key feature of Alzheimer's disease (AD), and enhanced cleavage of β‐amyloid precursor protein (APP) by β‐site APP‐cleaving enzyme 1 (BACE1) has a major causative role in AD. Despite their prominence in AD pathogenesis, the regulation of BACE1 and APP is incompletely understood. In this study, we report that the circular RNA circular RNA sponge for miR‐7 (ciRS‐7) has an important role in regulating BACE1 and APP protein levels. Previous studies have shown that ciRS‐7, which is highly expressed in the human brain, is down‐regulated in the brain of people with AD but the relevance of this finding was not clear. We have found that ciRS‐7 is not involved in the regulation of APP and BACE1 gene expression, but instead reduces the protein levels of APP and BACE1 by promoting their degradation via the proteasome and lysosome. Consequently, overexpression of ciRS‐7 reduces the generation of Aβ, indicating a potential neuroprotective role of ciRS‐7. Our data also suggest that ciRS‐7 modulates APP and BACE1 levels in a nuclear factor‐κB (NF‐κB)‐dependent manner: ciRS‐7 expression inhibits translation of NF‐κB and induces its cytoplasmic localization, thus derepressing expression of UCHL1, which promotes APP and BACE1 degradation. Additionally, we demonstrated that APP reduces the level of ciRS‐7, revealing a mutual regulation of ciRS‐7 and APP. Taken together, our data provide a molecular mechanism implicating reduced ciRS‐7 expression in AD, suggesting that ciRS‐7 may represent a useful target in the development of therapeutic strategies for AD. Abstract : The circular RNA ciRS‐7 promotes amyloid precursor protein (APP) and β‐site APP cleaving enzyme 1 (BACE1) degradation in a nuclear factor‐κB (NF‐κB)‐dependent manner. ciRS‐7 inhibits the protein translation of NF‐κB and induces its cytoplasmic localization. This releases NF‐κB‐repressed expression of ubiquitin carboxyl‐terminal hydrolase L1 (UCHL1), which promotes APP and BACE1 degradation via the proteasome and lysosome. APP in turn reduces the level of ciRS‐7.